What are teachers' perceptions and experiences of video in the classroom? - Bingham, Phillippa (2016)
This dissertation is an investigation into teachers’ perceptions and experiences of video in the classroom. Teachers’ opinions about filming themselves as part of their continuing professional development are explored as well as any perceived advantages or difficulties engaging with this technology. Primary qualitative research was conducted in a Midlands secondary school and sixth form with a view to investigating teachers’ views and experiences with video and the IRIS Connect system in particular. This inquiry was conducted using semi-structured interviews which were then thematically analysed and compared with a comprehensive review of the literature on video in schools, pedagogical theory and relevant contemporary issues in education. Conclusions were drawn about the nature and value of filming teachers/lessons and implications these might have on any CPD package offered within schools.